1988
DOI: 10.1101/gad.2.7.863
|View full text |Cite
|
Sign up to set email alerts
|

An erythrocyte-specific protein that binds to the poly(dG) region of the chicken beta-globin gene promoter.

Abstract: The promoter region of the chicken aduh p-globin gene contains a sequence of 16 deoxyguanosine residues located at a nucleosome boundary in tissues where the gene is inactive. In definitive erythrocytes that express the p-globin gene, the nucleosome is displaced, the G-string and adjacent sequences are occupied by sequencespecific DNA-binding proteins, and a nuclease hypersensitive domain is generated in this region. To gain insight into the role of the G-string in this series of events, we have examined the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
104
0
1

Year Published

1990
1990
1997
1997

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(108 citation statements)
references
References 33 publications
3
104
0
1
Order By: Relevance
“…Secondly, the Zn# + requirement for DNA binding of proteins 4 and 5 suggests that these two proteins could be zinc-finger transcription factors. Interestingly, the requirement for bivalent ions has also been shown for the G-string-binding factor BGP1, which needs Zn# + ions for its DNA-binding activity [23]. Furthermore it was shown that the sea-urchin G-string-binding factor suGF1 is also tightly complexed with a cation [26].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Secondly, the Zn# + requirement for DNA binding of proteins 4 and 5 suggests that these two proteins could be zinc-finger transcription factors. Interestingly, the requirement for bivalent ions has also been shown for the G-string-binding factor BGP1, which needs Zn# + ions for its DNA-binding activity [23]. Furthermore it was shown that the sea-urchin G-string-binding factor suGF1 is also tightly complexed with a cation [26].…”
Section: Discussionmentioning
confidence: 93%
“…In the chicken, two G-string-element-containing promoters have been described that are bound by the chicken erythrocyte protein called β-globin protein 1, BGP 1 [23,24]. In the sea urchin (Psammechinus miliaris) the purification of another G-stringbinding protein of 59.5 kDa, called sea-urchin G-string factor 1 (suGF1), has been described [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…We have found that the DNA-binding activity of CACD is inhibited by chelators of divalent cations and that low concentrations of zinc can restore binding activity (23a). The zinc-dependent DNA-binding activity of CACD is reminiscent of that demonstrated for several zinc finger proteins, including Spl and an activity, likely to be Spl, that binds the chicken CACCC element (28,34).…”
Section: Discussionmentioning
confidence: 96%
“…For these reasons, many laboratories have been interested in characterizing potential transcriptional regulatory proteins that bind to this sequence element. A number of such putative factors have been identified in many different cell types (4,8,9,17,21,34,35,38,47,55). Because we are interested in the regulation of 3-globin gene transcription, we have studied CACCC-binding proteins from MEL cells, a mouse erythroid precursor immortalized at the pre-erythroblast stage (36).…”
mentioning
confidence: 99%
“…A mouse hepatic nuclear protein, sTBP, similarly binds to a single-stranded telomeric sequence [16]. The chicken erythrocyte protein, BGP1, binds with a high affinity to single-stranded, guanine-rich tracts within the regulatory region of the flA globin gene [17]. Recently we purified a protein, termed QUAD, from rabbit liver chromatin, that binds specifically to the quadruplex form of the Here we report the isolation of a new protein from rabbit hepatocyte, designated p27, that binds preferentially to single-stranded, guanine-rich DNA but not to its double-or tetrahelical forms.…”
Section: Introductionmentioning
confidence: 99%